2012
DOI: 10.1557/jmr.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Defects and transport in PrxCe1−xO2−δ: Composition trends

Abstract: Nonstoichiometric mixed ionic and electronic conductors (MIECs) find use as oxygen permeation membranes, cathodes in solid oxide fuel cells, oxygen storage materials in three-way catalysts, and chemoresistive gas sensors. Praseodymium-cerium oxide (Pr x Ce 1Àx O 2Àd ) solid solutions exhibit MIEC behavior in a relatively high and readily accessible oxygen partial pressure (P O 2 ) regime and as such serve as model systems for investigating the correlation between thermodynamic and kinetic properties as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…This indicates that Ce will be more readily reduced upon a higher Pr concentration. A similar trend was also observed in purely Prdoped ceria 35 and purely Gd-doped ceria. 53 It is also found that the reducibility of Ce 4+ and Pr 4+ in ceria tends to be facilitated by the increasing oxygen nonstoichiometry, leading to a non-ideal reduction behavior.…”
supporting
confidence: 83%
“…This indicates that Ce will be more readily reduced upon a higher Pr concentration. A similar trend was also observed in purely Prdoped ceria 35 and purely Gd-doped ceria. 53 It is also found that the reducibility of Ce 4+ and Pr 4+ in ceria tends to be facilitated by the increasing oxygen nonstoichiometry, leading to a non-ideal reduction behavior.…”
supporting
confidence: 83%
“…This conclusion was also partially confi rmed with the results of ionic conductivities of Ce 1-x Pr x O 2-δ ( x = 0-0.2) shown in Figure 14 b. [ 373 ] The oxygen ionic conductivity fi rst increased by doping Pr into CeO 2 and reach the highest value for Pr 0.1 Ce 0.9 O 2-δ , then a decreased ionic conductivity was observed when 20% Ce was replaced by Pr. For instance, the electrical conductivity reached as high as 0.1 S cm −1 at 800 °C.…”
Section: Other Alkaline-earth-metal-free Metal Oxidessupporting
confidence: 68%
“…[ 374,375 ] The ionic conductivity reached ≈0.05 S cm −1 at 800 °C when the dopant concentration of Pr was 10%. [ 373 ] So, through appropriate ion REVIEW wileyonlinelibrary.com doping, the Pr doped cceria was possible to be used as oxygen reduction electrode for SOFCs. For example, an improved total conductivity (most likely the enhanced electronic conductivity) was obtained by adding 2 mol% CoO x into a Ce 0.9 Pr 0.1 O 2-δ phase.…”
Section: Other Alkaline-earth-metal-free Metal Oxidesmentioning
confidence: 99%
“…The low creep resistance questioning the actual use of BSCF in high temperature gas separation membranes and several attempts to stabilize BSCF by chemical substitution have appeared, both to avoid the formation of the hexagonal polymorph and to increase the creep resistance [22][23] . Chemical expansion [24][25] , particularly for ceria and perovskite materials with transition metals (Co, Fe) on the Bsite is another concern with respect to the mechanical stability of oxygen permeation membranes [26][27][28][29][30][31][32] . The chemical and thermal expansion of BSCF has also been reported by several groups [33][34][35][36][37][38] , showing lower chemical expansion than other similar candidate membrane materials due to smaller changes in oxygen stoichiometry and a generally larger unit cell, which is less sensitive to temperature and stoichiometry changes 38 .…”
Section: Introductionmentioning
confidence: 99%